Mass Media in Selected Muslim Countries - Mohd Yusof Hussain (IIUM, 2008)
This book documents the effort of six scholars to provide an understanding mass media development in nine Muslim countries. Undeniably, most students of the media even in Muslim countries, are more knowledgeable about the media the Western countries than they are about the media in Muslim countries.